Breaking the Silence on Spiritual Abuse - Oakley, L.; Kinmond, K.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Providing a balance of empirical research and practical concerns, this book explores the definitions and historical context of spiritual abuse, outlines a process model for the different stages of spiritual abuse and includes strategies for therapists working with survivors of spiritual abuse.
Keywords: Religion and sociology; Clinical psychology; Ethics; Social work; Personality; Social psychology; Supervision; Counseling; Sociology of Religion; Clinical Psychology; Ethics; Social Work; Personality and Social Psychology; Consulting, Supervision and Coaching